IMPROVE MATHEMATICAL LEARNING ACTIVITIES THROUGH THINK PAIR SHARE (TPS) COOPERATIVE LEARNING MODELS OF STUDENTS IN CLASS VIIIC OF SMP NEGERI 1 SELOMERTO WONOSOBO - Yuda Aji Pamungkas; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2017)
This reasearch was conducted because of the low activity of student learning in mathematics at school. For that it need an efforts to improve students' learning activeness. This study aims to improve the activeness of mathematics learning in sudent of class VIIIC of SMP Negeri 1 Selomerto Wonosobo through Think Pair Share (TPS) cooperative learning model of semester II in academic year of 2015/2016. This reasearch was a classroom action research consisted of two cycles. The subject of this research is class VIIIC of SMP Negeri 1 Selomerto Wonosobo in academic year of 2015/2016. While the object under study is the effort to increase the activity of learning mathematics through cooperative learning model TPS. Instruments used observation sheet and questionnaire. Data were analyzed using data reduction, data presentation, and conclusion triangulation. The results showed that the learning model TPS can increase the activeness of mathematics learning for students in class VIIIC in second semester of SMP Negeri 1 Selomerto Wonosobo in the academic year of 2015/2016. Percentage activity of learning mathematics increased each cycle. In the first cycle with an average of 49.74% with a criterion being, in Cycle II was increased so that the second cycle the average percentage of 65.97% with high criteria.